Intramuscular Hemangioma in Lip Treated with Sclerotherapy and Surgery - Silva, Vanessa A. (Hindawi Publishing Corporation, 2011)
Intramuscular hemangioma is a relatively rare, benign tumor of vascular origin, accounting for less than 1% of all hemangiomas. This paper reports a case of a 48-year-old female patient with intramuscular hemangioma in the upper lip, treated with sclerotherapy and subsequent complementary surgery.